2023
DOI: 10.1093/brain/awad381
|View full text |Cite
|
Sign up to set email alerts
|

Distinct involvement of the cranial and spinal nerves in progressive supranuclear palsy

Hidetomo Tanaka,
Ivan Martinez-Valbuena,
Shelley L Forrest
et al.

Abstract: The most frequent neurodegenerative proteinopathies include diseases with deposition of misfolded tau or α-synuclein in the brain. Pathological protein aggregates in the peripheral nervous system (PNS) are well-recognized in α-synucleinopathies and have recently attracted attention as a diagnostic biomarker. However, there is a paucity of observations in tauopathies. To characterize the involvement of the PNS in tauopathies, we investigated tau pathology in cranial and spinal nerves (PNS-tau) in 54 tauopathy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The expression level of substrates can amplify the pathogenic seed and contribute to the selected vulnerability of different neuronal populations 24,25 , and we previously showed higher concentrations of tau protein and higher levels of 4R tau transcripts in skin lysates of PSP and CBD vs synucleinopathies and HC 22 . In support of these results, another recent study has shown the presence of phosphorylated and 4R deposits in autoptic peripheral nerves, namely cranial and anterior spinal root nerves, of patients with PSP 26 . Nevertheless, few works in literature have explored the diagnostic capacities of 4R substrates in PSP and CBD in brain, and no one in skin.…”
Section: Discussionsupporting
confidence: 66%
“…The expression level of substrates can amplify the pathogenic seed and contribute to the selected vulnerability of different neuronal populations 24,25 , and we previously showed higher concentrations of tau protein and higher levels of 4R tau transcripts in skin lysates of PSP and CBD vs synucleinopathies and HC 22 . In support of these results, another recent study has shown the presence of phosphorylated and 4R deposits in autoptic peripheral nerves, namely cranial and anterior spinal root nerves, of patients with PSP 26 . Nevertheless, few works in literature have explored the diagnostic capacities of 4R substrates in PSP and CBD in brain, and no one in skin.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, iron accumulation has also been observed along the oculomotor nerve of six PSP brains, which has not been observed in aged controls [88]. A recent study by Tanaka et al [89] demonstrates the PSP-specific involvement of tau deposition in the cranial and spinal nerves, including the oculomotor nerve, supporting a tight association between iron and tau in PSP. Accordingly, the correlations between susceptibility and flortaucipir uptake were shown to be significantly positive in the putamen, pallidum, subthalamic nucleus, RN, and the dentate nucleus of PSP patients, and it was suggested that susceptibility measures may mediate or explain the levels of flortaucipir uptake [87].…”
Section: Iron Dysregulation In Pspmentioning
confidence: 86%